2018
DOI: 10.1108/jcrpp-07-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

The Life in Custody Study: the quality of prison life in Dutch prison regimes

Abstract: Purpose The Life in Custody (LIC) Study is a nationwide prospective cohort study examining the quality of prison life in the Netherlands. The purpose of this paper is to describe Dutch prisoners’ perceptions of prison climate, as well as differences across regimes. Design/methodology/approach The target population of the study consisted of all male and female adult prisoners in the Netherlands who were incarcerated in various regimes in a total of 28 prisons, between January and April 2017. An intensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 52 publications
(56 reference statements)
1
50
0
3
Order By: Relevance
“…Therefore, both survey and registration data were available for a sample of 4,538 prisoners. Table 1 (prisoner characteristics) shows relevant sample characteristics for study participants (for more information regarding the representativeness of the Life in Custody (LIC) study sample, see Van Ginneken et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, both survey and registration data were available for a sample of 4,538 prisoners. Table 1 (prisoner characteristics) shows relevant sample characteristics for study participants (for more information regarding the representativeness of the Life in Custody (LIC) study sample, see Van Ginneken et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To do so, the Prison Climate Questionnaire (PCQ; Anonymous) was administered to the full population of prisoners (males and females, pre-trial detention and convicted, in practically all regimes and populations 1 ) housed in each of the 28 prisons operational in the Netherlands between January and April 2017. An extensive overview of the LIC study can be found in van Ginneken et al (2018).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Consequently, the aim of this article is to assess the extent to which prisoner characteristics (personal characteristics and prison climate) and prison environment are related to prisoner misconduct. This is studied by using data from the Life In Custody [LIC] study (van Ginneken et al, 2018), a nationwide prospective cohort study examining the experience of prison climate in the Netherlands. By using this dataset, we have access to self-report data, as well as official reports on four types (verbal, physical, property, and contraband) of prisoner misconduct.…”
Section: The Current Studymentioning
confidence: 99%
“…It is logical to assume that overall QOL would be intricately tied to the influence of one’s immediate surroundings as noted in the aforementioned discussion of carceral climate. As van Ginneken and colleagues (2018) note, QOL was attenuated among incarcerated persons who reported lower levels of autonomy, safety, meaningful activities, and interpersonal relationships as they related to the prison environment. And persons who were incarcerated in minimum security prisons reported higher overall levels QOL in terms of both psychological well-being and environmental satisfaction than those in more restrictive carceral environments (van Ginneken et al, 2018).…”
Section: Discussionmentioning
confidence: 95%